MBRole: enrichment analysis of metabolomic data - Chagoyen, Monica; Pazos, Florencio (Bioinformatics (Oxford, England), 2011)
While many tools exist for performing enrichment analysis of transcriptomic and proteomic data in order to interpret them in biological terms, almost no equivalent tools exist for metabolomic data. We present Metabolite Biological Role (MBRole), a web server for carrying out over-representation analysis of biological and chemical annotations in arbitrary sets of metabolites (small chemical compounds) coming from metabolomic data of any organism or sample. Availability and Implementation: The web server is freely available at http://csbg.cnb.csic.es/mbrole. It was tested in the main web browsers. Contact:  monica.chagoyen@cnb.csic.es